Shattered Past : Reconstructing German Histories - Jarausch, Konrad Hugo (Book collections on Project MUSE., 2003)
Broken glass, twisted beams, piles of debris--these are the early memories of the children who grew up amidst the ruins of the Third Reich. More than five decades later, German youth inhabit manicured suburbs and stroll along prosperous pedestrian malls. Shattered Past is a bold reconsideration of the perplexing pattern of Germany's twentieth-century history. Konrad Jarausch and Michael Geyer explore the staggering gap between the country's role in the terrors of war and its subsequent success as a democracy.